The Role of Psychological Factors on The Psychological and Social Adjustment Through The Mediation of Ischemic Heart Disease Hypertension - Sara Sahranavard; Hasan Ahadi; Mohamad hosein Taghdisi; Toba kazemi; Addis kraskian (Iranian Association of Health Education and Health Promotion, 2017)
Ischemic heart disease is a psycho-physiological problem. There are several biological and psychological factors that affect the incidence and severity of hypertension. The present study was aimed to the role of psychological and social factors mediating effect of physical factors is the compatibility of ischemic heart disease. Methods: In this descriptive-correlated study ,The study population included over- 30 - adult pation with Ischemic heart disease  who referred to health center in khorasan jonobi. Through convenience sampling 310 persons were selected as samples of the study.  health locus of control and social perception of mental illness and cope were used to gather the data. To analyze the data Structural equation modeling (SEM) Amos18 was done by software was used. Results: There was a significant negative correlation between blood pressure and psychosocial adjustment there (05/0> p, 17 / 0- = B). Between psychological factors and psychological and social adjustment there is a significant positive relationship. (05/0> p; 95 / 0- = B). BP relationship between psychological factors mediate the relationshipcompatibility.(05/0>p) Conclusion: Health locus of control and perception of a significant relationship with psychological and social adjustment, and also a significant relationship between blood pressure and psychological and social adjustment there. As well as psychological factors mediating effect of blood pressure on the compatibility of ischemic heart disease are associated and severity of the impact of 05 / 0- respectively. PaperType:ResearchArticle.